The Murine Gammaherpesvirus 68 v-Cyclin Gene Is an Oncogene That Promotes Cell Cycle Progression in Primary Lymphocytes - van Dyk, Linda F. (American Society for Microbiology, 1999)
Several gammaherpesviruses contain open reading frames encoding proteins homologous to mammalian D-type cyclins. In this study, we analyzed the expression and function of the murine gammaherpesvirus 68 (γHV68) viral cyclin (v-cyclin). The γHV68 v-cyclin gene was expressed in lytically infected fibroblasts as a leaky-late mRNA of approximately 0.9 kb encoding a protein of approximately 25 kDa. To evaluate the effect of the γHV68 v-cyclin on cell cycle progression in primary lymphocytes and to determine if the γHV68 v-cyclin gene is an oncogene, we generated transgenic mice by using the lck proximal promoter to express the γHV68 v-cyclin in early T cells. Expression of the γHV68 v-cyclin significantly increased the number of thymocytes in cell culture, as determined by measuring both DNA content and incorporation of 5-bromo-2-deoxyuridine following in vivo pulse-labeling. Expression of the γHV68 v-cyclin interfered with normal thymocyte maturation, as shown by increased numbers of CD4(+) CD8(+) double-positive thymocytes and decreased numbers of CD4(+) or CD8(+) single-positive and T-cell-receptor-bright thymocytes and splenocytes in transgenic mice. Despite increased numbers of cycling thymocytes, γHV68–v-cyclin–transgenic mice did not have proportionately increased thymocyte numbers, and staining by terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling demonstrated increased apoptosis in the thymi of v-cyclin-transgenic mice. Fifteen of 38 γHV68–v-cyclin–transgenic mice developed high-grade lymphoblastic lymphoma between 3 and 12 months of age. We conclude that (i) the γHV68 v-cyclin is expressed as a leaky-late gene in lytically infected cells, (ii) expression of the γHV68 v-cyclin in thymocytes promotes cell cycle progression and inhibits normal T-cell differentiation, and (iii) the γHV68 v-cyclin gene is an oncogene.